Direct and bystander effects in human blood lymphocytes exposed to 241Am alpha particles and the relative biological effectiveness using chromosomal aberration and micronucleus assay. (3rd June 2019) - Karthik, K.; Rajan, Vasumathy; Pandey, Badri N.; Sivasubramanian, K.; Paul, Solomon F.D.; Venkatachalam, P.
Abstract: Purpose: It is important to understand the significance of alpha (α) radiation-induced bystander effects (RIBE) and its relative biological effectiveness (RBE); this is because the phenomenon is not universal and the mechanism is unclear and because the RBE is widely varying and projected to be very high. Materials and methods: Isolated lymphocytes from healthy volunteers ( n = 10) were exposed to either low fluence α-particles ( 241 Am), γ-rays ( 60 Co), or X-rays (225 kVp and 6 MV). Co-culture methodology was employed to investigate bystander effects (BEs). Chromosomal aberrations (CA) and micronucleus (MN) formation were used to study the BE and calculated RBE. Results: Lymphocytes directly exposed to the types of radiation used showed a dose-dependent increase in the frequency of CA and MN; dose independent increases in the frequency of these chromosomal damages in co-cultured bystander cells, implies that all three types of radiation-induced a BE. The calculated RBE at the level of 5% induced aberrations varied between 9 and 20. Conclusion: The magnitude of low fluence α-particle induced RIBE is higher than in low LET (linear energy transfer) radiation. The RBE also varies depending upon the endpoints used and adds up to targeted effects. Since the endpoint of CA is considered as an important and early marker of risk prediction, the RIBE and RBE using CA as a marker are relevant for radiation protection purposes.